The social integration of Syrian refugees in Germany - Theresa Kuchler; Johannes Stroebel (EconPol Forum, 2022)
Syrians in Germany generally have low levels of social integration compared to German natives, measured by the number of Facebook connections/groups and content posted in German. Social integration in rural regions is higher than in more urban regions ¦ The degree of integration in a region is driven by the local environment, less by the behavior of local natives or the present Syrian population. The availability of integration courses causally drives local integration. Direct personal contact with locals helps integration.
Keywords: 330